Photocatalytic Radical Addition to Levoglucosenone. Issue 1 (16th December 2021) - Lefebvre, Corentin; Van Gysel, Terence; Michelin, Clément; Rousset, Elodie; Djiré, Djibril; Allais, Florent; Hoffmann, Norbert
Abstract: Using photocatalysis with tetra‐n‐butylammonium decatungstate (TBADT), alkanes, cyclic acetals, cyclic ethers, formamide and aldehydes were added in a stereoselective way to levoglucosenone (LGO). A hydrogen atom is transferred from the donor compound to the photochemically excited TBADT, and the resulting radicals add onto LGO in a stereoselective way. In the case of the addition of adamantane, two regio‐isomers were obtained which form a crystalline solid solution. Cyrene™, obtained by hydrogenation of LGO, was added under the same conditions. In this case, only two of 32 possible isomers of the resulting Cyrene™ dimer were formed. The regio‐selectivity of the HAT step is discussed in detail. For this purpose, bond dissociation energies and partial charges have been calculated. Transition state calculations of the radical addition to LGO explain the stereospecificity of this reaction step. Abstract : Photocatalytic hydrogen atom transfer (HAT) transfer is applied to the stereoselective addition of alkanes, acetales, ethers, formamide and aldehydes to levoglucosenone. Bond dissociation energies and partial charges have been calculated in order to discuss the highly selective HAT at cyrene TM .